2024
DOI: 10.1021/acsnano.4c00699
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles Engineered Macrophage-Derived Exosomes for Targeted Pathological Angiogenesis Therapy

Haorui Zhang,
Yu Mao,
Zheng Nie
et al.

Abstract: Engineering exosomes with nanomaterials usually leads to the damage of exosomal membrane and bioactive molecules. Here, pathological angiogenesis targeting exosomes with magnetic imaging, ferroptosis inducing, and immunotherapeutic properties is fabricated using a simple coincubation method with macrophages being the bioreactor. Extremely small iron oxide nanoparticle (ESIONPs) incorporated exosomes (ESIONPs@EXO) are acquired by sorting the secreted exosomes from M1-polarized macrophages induced by ESIONPs. ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In addition to their ability to cross the BBB, EV use is favorable because of low immunogenicity, biodegradability, and their non-toxic nature. Further, they can carry cargo, such as iron particles in this study and others 24,26,28,31,32,52,53 , as well as therapeutics 17,18,[20][21][22][23]25,50,51 . The mechanisms in which EVs cross the BBB is not fully understood; however, some possible routes which have been explored are micropinocytosis, clathrin-dependent endocytosis and caveolae-dependent endocytosis 15,16,54,55 .…”
Section: Association Of Iron With Evs Allows Iron To Accumulate In Th...mentioning
confidence: 71%
See 2 more Smart Citations
“…In addition to their ability to cross the BBB, EV use is favorable because of low immunogenicity, biodegradability, and their non-toxic nature. Further, they can carry cargo, such as iron particles in this study and others 24,26,28,31,32,52,53 , as well as therapeutics 17,18,[20][21][22][23]25,50,51 . The mechanisms in which EVs cross the BBB is not fully understood; however, some possible routes which have been explored are micropinocytosis, clathrin-dependent endocytosis and caveolae-dependent endocytosis 15,16,54,55 .…”
Section: Association Of Iron With Evs Allows Iron To Accumulate In Th...mentioning
confidence: 71%
“…Iron-labeled EVs have been imaged previously using MRI [25][26][27]30,31 and MPI 32 . Methods used to label EVs have been through direct labeling, or indirect labeling where the parental cell is co-incubated with the iron and is allowed to take up the nanoparAcle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [99], exosomes derived from macrophages were electroporated with extremely small iron oxide nanoparticles (ESIONPs@EXO) which induce ferroptosis. It was shown that treatment with ESIONPs@EXO resulted in M2 to M1 reprogramming, significantly inhibited vessel formation, reduced endothelial cell sprouting, and suppressed pathological angiogenesis in vivo via VEGF-independent mechanism in the ocular melanoma model, also prohibiting tumor cell proliferation and migration.…”
Section: Nanotherapy Options Aimed At Targeting Tams 61 Tam Reprogram...mentioning
confidence: 99%
“…Because EVs can circulate in the bloodstream for a prolonged period of time, can cross the BBB, ,, and can be manipulated as carriers of drugs, nucleic acids, or nanoparticles, there is vast potential to engineer EVs as imaging or delivery tools to target brain metastases. Previous studies have labeled EVs with superparamagnetic iron oxide (SPIO) nanoparticles for in vivo tracking using magnetic resonance imaging (MRI) ,, and to a lesser extent, magnetic particle imaging (MPI) . Additionally, EVs derived from tumor cells have been shown to improve delivery to parental tumor cells in vivo. A recent study has used photoacoustic imaging to detect Prussian blue nanoparticles within an orthotopic brain tumor model in mice .…”
Section: Introductionmentioning
confidence: 99%